Nutritional status and physical activity of childhood leukemia survivors - Conny Tanjung; Johannes Bondan Lukito; Prima Dyarti Meylani (Indonesian Pediatric Society, 2014)
Background Acute lymphoblastic leukemia (ALL), the mostcommon malignancy of childhood, has an overall cure rate ofapproximately 80%. Long-term survivors of childhood ALL areat increased risk for obesity and physical inactivity that may leadto the development of diabetes, dyslipidemia, metabolic syndrome,as well as cardiovascular dis eases, and related mortality in theyears following treatment.Objective To evaluate the physical activity and the propensityfor developing obesity longer term in ALL survivors.Methods This retrospective cohort study included all ALLsurvivors from Pantai Indah Kapuk (PIK) Hospital. We assessedtheir physical activity and nutritional status at the first time ofALL diagnosis an d at the time of interview.Results Subjects were 15 ALL survivors aged 7 to 24 years. Themedian fo llow up time was 6.4 years (range 3 to 10 years). Only2 out of 15 survivors were overweight and n one were obese.All survivors led a sedentary lifestyle. Most female subjectshad increased BMI, though most were not overweight/obese.Steroid therapy in the induction phase did not increase the riskof developing obesity in ALL survivors.Conclusion Lon g-term survivors of childh ood ALL do not meetphysical activity recommendations according to the CDC (Centersfor Disease Control). Howevei; steroid therapy do not seem tolead to overweight/obesity in ALL survivors.